Influence of oil-based and water-based lubrication on tool wear of DLC/TiAlN-coated punches in blanking of stainless steel - Ibrahim, Muhammad Shuhaimi; Sulaiman, Mohd Hafis; Ismail, Mohd Idris Shah (Malaysian Tribology Society, 2025)
This study aims to eliminate the use of oil-based lubricants in the metal forming process by integrating a new tribological system of double-layered Carbon/Titanium Aluminum Nitride (DLC/TiAlN) with water-based lubrication. The research compared the performance of traditional oil-based lubricant (cutting fluids) against water-based lubricants containing Magnesium Oxide (MgO) and Silicon Carbide (SiC) nanoparticles. This waterbased lubricant, prepared through a two-step method, is applied to the surface of 1 mm thick SUS304 stainless steel during the blanking process. A mixture of MgO and SiC reduces the coefficient of friction more effectively than when using a single additive. The combined effect of using DLC/TiAlN-coated tools with water-based lubricants with MgO/SiC additives increases resistance to galling, leading to a 14% reduction in draining force compared to dry friction and a 3% reduction compared to cutting fluids. Moreover, the combination of MgO/SiC minimizes the formation of burrs at the edge of the product during the blanking process. The water-based lubricants with MgO/SiC are a competitive alternative to oil-based lubricants in the metal forming industry.